2010
DOI: 10.3109/00016357.2010.535560
|View full text |Cite
|
Sign up to set email alerts
|

Oral health: locus of control, health behavior, self-rated oral health and socio-demographic factors in Istanbul adults

Abstract: Compared with the original factor structure, the new factor structure had better goodness of fit for this sample. Self-rated oral health, socio-demographic factors, and oral health behaviors were significantly associated with oral health control beliefs. These beliefs may be useful for planning oral health promotion programs and for formulating advice given by oral health professionals about their patients' oral health behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 30 publications
4
19
1
2
Order By: Relevance
“…A more external locus of control as shown by higher SILOC scores was associated with higher dental neglect, caries, and plaque and gingivitis prevalence as well as with a tendency to postpone needed dental treatment. Previous research has shown that an external locus of control was associated with poorer oral health indicators [11,13,14] well as poorer dental attendance [17,29,30], which were in agreement with the findings of our study. These factors were considered for validation of the SILOC as they have been shown to be associated with locus of control in the past.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…A more external locus of control as shown by higher SILOC scores was associated with higher dental neglect, caries, and plaque and gingivitis prevalence as well as with a tendency to postpone needed dental treatment. Previous research has shown that an external locus of control was associated with poorer oral health indicators [11,13,14] well as poorer dental attendance [17,29,30], which were in agreement with the findings of our study. These factors were considered for validation of the SILOC as they have been shown to be associated with locus of control in the past.…”
Section: Discussionsupporting
confidence: 83%
“…These factors were considered for validation of the SILOC as they have been shown to be associated with locus of control in the past. Females demonstrated lower SILOC scores signifying greater internality than males which were in agreement with the findings reported by Peker and Bermek [30]. These findings may be explained by the fact that females tend to have better health compliance than males.…”
Section: Discussionsupporting
confidence: 83%
“…Estes resultados podem refletir a importância do desenvolvimento psicológico e social durante o envelhecimento, concomitantemente ao aumento da necessidade de tratamento restaurador e protético [10]. À medida em que a pessoa envelhece, há uma tendência a aumentar a necessidade de tratamento odontológico, relacionada a perdas das funções do sistema estomatognático, como mastigar, deglutir e conversar, além de aspectos de estética e socialização.…”
Section: Artigo Originalunclassified
“…Crenças sobre percepção de controle de saúde são consideradas um importante fator motivacional para a compreensão da adoção de comportamentos de promoção da saúde pelos idosos [10]. O locus de controle de saúde é capaz de indicar se os indivíduos vão ou não tomar responsabilidade por sua própria saúde [11,12].…”
Section: Introductionunclassified
“…In the past decade, few studies using validated subjective oral health measures have been conducted to verify the impact of different oral disorders and prosthodontic treatments on oral health quality of life in Turkish patients groups (Arslan et al, 2009;Baran & Nalcaci, 2011;Caglayan et al, 2009;Geckili et al, 2011). To the best of your knowledge, there is one published study that investigated the relationships among oral health beliefs, oral health behaviors, sociodemographic factors and SROH (Peker & Bermek, 2011). SROH is an assessment of the functional, psychological, and social impact of oral disease and disorder on overall well being (Locker & Gibson, 2005).…”
Section: Introductionmentioning
confidence: 99%